Free‐breathing whole‐heart multi‐slice myocardial T1 mapping in 2 minutes. Issue 1 (14th July 2020) - Guo, Rui; Cai, Xiaoying; Kucukseymen, Selcuk; Rodriguez, Jennifer; Paskavitz, Amanda; Pierce, Patrick; Goddu, Beth; Nezafat, Reza
Abstract : Purpose: To develop and validate a saturation‐delay‐inversion recovery preparation, slice tracking and multi‐slice based sequence for measuring whole‐heart native T1 . Method: The proposed free‐breathing sequence performs T1 mapping of multiple left‐ventricular slices by slice‐interleaved acquisition to collect 10 electrocardiogram‐triggered single‐shot slice‐selective images for each slice. A saturation‐delay‐inversion recovery pulse is used for T1 preparation. Prospective slice tracking by the diaphragm navigator and retrospective registration are used to reduce through‐plane and in‐plane motion, respectively. The proposed sequence was validated in both phantom and human subjects (12 healthy subjects and 15 patients who were referred for a clinical cardiac MR exam) and compared with saturation recovery single‐shot acquisition (SASHA) and modified Look‐Locker inversion recovery (MOLLI). Results: Phantom T1 measured by the proposed sequence had excellent agreement ( R 2 = 0.99) with the ground‐truth T1 and was insensitive to heart rate. In both healthy subjects and patients, the proposed sequence yielded nine left‐ventricular T1 maps per volume in less than 2 minutes (healthy volunteers: 1.8 ± 0.4 minutes; patients: 1.9 ± 0.2 minutes). The average T1 of whole left ventricle for all healthy subjects and patients were 1560 ± 61 and 1535 ± 49 ms by SASHA, 1208 ± 42 and 1233 ± 56 ms by MOLLI5(3)3, and 1397 ± 34 and 1433 ± 56 ms by the proposed sequence, respectively. The corresponding coefficient of variation of T1 were 6.2 ± 1.4% and 5.8 ± 1.6%, 5.3 ± 1.1% and 5.1 ± 0.8%, and 4.9 ± 0.8% and 4.5 ± 0.8%, respectively. Conclusion: The proposed sequence enables quantification of whole heart T1 with good accuracy and precision in less than 2 minutes during free breathing.